A weighted cranial diffusion-weighted imaging scale for Wilson’s disease - Wang, Shi-jing; Geng, Hao; Cheng, Si-rui; Xu, Chen-chen; Zhang, Rui-qi; Wang, Yu; Wu, Tong; Li, Bo; Wang, Tao; Han, Yong-sheng; Ding, Zeng-hui; Sun, Yi-ning; et al. (Frontiers in Neuroscience, 2023)
Objectives Cranial magnetic resonance imaging (MRI) could be a crucial tool for the assessment for neurological symptoms in patients with Wilson’s disease (WD). Diffusion-weighted imaging (DWI) hyperintensity reflects the acute brain injuries, which mainly occur in specific brain regions. Therefore, this study aimed to develop a weighted cranial DWI scale for patients with WD, with special focus on specific brain regions. Materials and methods In total, 123 patients with WD were enrolled, 118 of whom underwent 1.5 T-MRI on admission. The imaging score was calculated as described previously and depended on the following sequences: one point was acquired when abnormal intensity occurred in the T1, T2, and fluid-attenuation inversion recovery sequences, and two points were acquired when DWI hyperintensity were found. Consensus weighting was conducted based on the symptoms and response to treatment. Results Intra-rater agreement were good (r = 0.855 [0.798–0.897], p < 0.0001). DWI hyperintensity in the putamen was a high-risk factor for deterioration during de-copper therapy (OR = 8.656, p < 0.05). The high-risk factors for readmission for intravenous de-copper therapies were DWI hyperintensity in the midbrain (OR = 3.818, p < 0.05) and the corpus callosum (OR = 2.654, p < 0.05). Both scoring systems had positive correlation with UWDRS scale (original semi-quantitative scoring system, r = 0.35, p < 0.001; consensus semi-quantitative scoring system, r = 0.351, p < 0.001.). Compared to the original scoring system, the consensus scoring system had higher correlations with the occurrence of deterioration (OR = 1.052, 95%CI [1.003, 1.0103], p < 0.05) and readmission for intravenous de-copper therapy (OR = 1.043, 95%CI [1.001, 1.086], p < 0.05). Conclusion The predictive performance of the consensus semi-quantitative scoring system for cranial MRI was improved to guide medication, healthcare management, and prognosis prediction in patients with WD. For every point increase in the neuroimaging score, the risk of exacerbations during treatment increased by 5.2%, and the risk of readmission to the hospital within 6 months increased by 4.3%.